Sharice's big voice : a native kid becomes a congresswoman [book with audioplayer] - Davids, Sharice, 1980-; Mays, Nancy K. ([Library Ideas, LLC], 2021)
This inspiring picture book autobiography tells the remarkable story of Sharice Davids, one of the first Native American women elected to Congress and the first LGBTQ congressperson to represent Kansas.